Delusions Redux. (1st February 2013) - Radden, Jennifer
Abstract: My response to the preceding essays begins with some preliminaries about my terminology, approach, and conception of rationality as a regulative ideal. I then comment on the Murphy's discussion about normal religious belief and religious delusions, and on causal assumptions challenged by Langdon's folies à deux. Responding to Gerrans's imagination‐based account of delusion and Hohwy's discussion of illusions, I next try to envision what both doxastic and imagination‐based approaches might have overlooked by asking whether there can be delusional feelings. Final comments address the place of phenomenology within Coltheart's two‐factor theorizing.